2007
DOI: 10.1007/s10067-007-0664-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful full-term pregnancy in a woman with Cogan’s syndrome: a case report

Abstract: Cogan's syndrome (CS) is a chronic inflammatory disorder that most commonly affects young adults. Major clinical features are interstitial keratitis and vestibuloauditory dysfunction. Associations between CS and systemic vasculitis as well as aortitis also exist. The present report is the first case in the literature of pregnancy associated with Cogan syndrome, which posed a therapeutic challenge. There was a relapse of the ocular symptoms only during the first trimester of pregnancy, but the pregnancy was oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…A search of the literature revealed only three other reports of pregnancy in combination with CS to date 12–14. Apart from one case of uncomplicated interstitial keratitis similar to the case reported here, all three pregnancies were uneventful.…”
Section: Discussionsupporting
confidence: 49%
“…A search of the literature revealed only three other reports of pregnancy in combination with CS to date 12–14. Apart from one case of uncomplicated interstitial keratitis similar to the case reported here, all three pregnancies were uneventful.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, in this cohort, two out of the three miscarriage occurs in the same women who had Cogan syndrome, a rare and severe autoimmune disease. In the literature, only eight cases of successful pregnancy with this disease have been reported [ 86 , 87 , 88 , 89 , 90 , 91 ]. Thus, it cannot be concluded that the therapy caused pregnancy loss in these women.…”
Section: Discussionmentioning
confidence: 99%
“…Half of previously reported CS patients did not need any systemic immunosuppressive treatments throughout pregnancy, instead intermittent topical treatment with ophthalmic steroids was sufficient ( 10 13 ). Other pregnant patients in remission were successfully treated with hydroxychloroquine, or a combination therapy of either cyclosporine or intravenous immunoglobulin application (IVIG) with azathioprine and prednisolone ( 8 , 9 , 12 ).…”
Section: Discussionmentioning
confidence: 99%